Studying the Effects of El Nino Southern Oscillation on Precipitation based on Southern Oscillation Index: Case Study for the Region of Shahr-e-Kord in Iran - Sadi, Tofigh; Arzjani, Zahra; Zadeh, Maryam Mosa (International Journal of Bio-resource and Stress Management, 2023)
El Nino Southern Oscillation (ENSO) phenomena is one of the atmospheric events causing climatic variability Worldwide that demonstrates a teleconnection pattern on a global scale. It influences the whole southern hemisphere and a great part of northern hemisphere beyond countries and continents. The present research investigates the impacts of this phenomenon on precipitation in Shahr-e-Kord region, southwest Iran using Southern Oscillation Index. Monthly precipitation records of Shahr-e-Kord gauging station for a period of 1956-2005 were gathered for the purpose of this study and the results showed that a significant correlation of 0.01 and 0.05 exists for precipitation data of several months of the year over specific time periods. This correlation is negative which emphasizes the fact that the El Nino event is usually followed by a wet year and the La Nina phenomenon reduces the precipitation in the region.